Biological monitoring of low-level exposure to benzene / Monitoraggio biologico dell’esposizione a basse dosi di benzene - Campagna, Marcello; Satta, Giannina; Campo, Laura; Flore, Valeria; Ibba, A.; Meloni, M.; Tocco, Maria Giuseppina; Avataneo, G.; Flore, C.; Fustinoni, Silvia; Cocco, Pierluigi (La Medicina del Lavoro, 2012)
SummaryIntroduction: Conflicting opinions exist about the reliability of biomarkers of low-level  exposure to benzene. We compared the ability of the urinary excretion of trans,trans-muconic acid (t,t-MA), s-phenilmercapturic acid (s-PMA) and urinary benzene (U-Benz) to detect low level occupational and environmental exposure to benzene. Methods: We monitored airborne benzene by personal air sampling, and U-Benz, s-PMA, t,t-MA and cotinine (U-Cotinine) in spot urine samples, collected at 8 am and 8 pm, in 32 oil refinery workers and 65 subjects, randomly selected among the general population of urban and suburban Cagliari, Italy. Information on personal characteristics, diet and events during the sampling day was acquired through in person interviews. Results: The median concentration of airborne benzene was 25.2 mg/m3 in oil refinery workers, and 8.5 mg/m3 in the general population subgroup. U-Benz in morning and evening samples was significantly more elevated among oil refinery workers than the general population subgroup (p=0.012, and p=7.4x10-7, respectively) and among current smokers compared to non-smokers (p=5.2x10-8, and p=5.2x10-5 respectively). Benzene biomarkers and their readings in the two sampling phases were well correlated to each other. The Spearman’s correlation coefficient with airborne benzene was significant for U-Benz in the evening sample, while no correlation was seen with t,t-MA and s-PMA readings in either samplings. The two benzene metabolites were frequently below limit of detection (LOD), particularly among the general population study subjects (17-9% and 39%, for t,t-MA and s-PMA respectively). Morning U-Cotinine excretion showed a good correlation with U-Benz in the morning and in the evening sampling (p